2017
DOI: 10.1177/1089253217720284
|View full text |Cite
|
Sign up to set email alerts
|

Severe Aortic Valve Stenosis Due to Alkaptonuric Ochronosis

Abstract: Alkaptonuric ochronosis is a rare cause of aortic valve stenosis. We report the case of a 61-year-old female patient with alkaptonuria who presented to our institute with the clinical picture of severe aortic valve stenosis, which was confirmed by transthoracic echocardiography. On aortotomy, she was noted to have an impressive black discoloration of ascending aorta and the aortic root complex involving the aortic valve leaflets. She underwent an uneventful aortic valve replacement. She was discharged home 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Accumulation of HGA causes the classic clinical triad: homogentisic aciduria, gradual development of ochronosis, and degenerative ochronotic arthropathies. Cardiac involvement in alkaptonuria is rare and mainly manifested as valvular calcification [13]. As renal clearance of HGA decreases with age, clinical manifestations of alkaptonuric ochronosis are usually delayed, not appearing until the fourth decade of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of HGA causes the classic clinical triad: homogentisic aciduria, gradual development of ochronosis, and degenerative ochronotic arthropathies. Cardiac involvement in alkaptonuria is rare and mainly manifested as valvular calcification [13]. As renal clearance of HGA decreases with age, clinical manifestations of alkaptonuric ochronosis are usually delayed, not appearing until the fourth decade of life [14].…”
Section: Discussionmentioning
confidence: 99%
“…The authors present the surgical case for this patient that was found to have alkaptonurin ochronosis and present very unique descriptive findings at surgery as well as the pathologic basis of the disease. 15…”
mentioning
confidence: 99%
“…The authors present the surgical case for this patient that was found to have alkaptonurin ochronosis and present very unique descriptive findings at surgery as well as the pathologic basis of the disease. 15 In our December issue of the SCVA, we have compiled contemporary articles on perioperative noninvasive hemodynamic monitoring, on management of patients presenting with different preexisting heart conditions undergoing cardiac surgery or related procedures, on dexmedetomidine use in pediatric cardiac catheterization procedures, and genetically driven variability in dexmedetomidine response in pediatric patients. With the overarching goal of SCVA to support the mission of the Society for the Advancement of Transplant Anesthesia, our journal is also publishing a white paper advocating measurable proficiency in training of future to be fellows in liver transplant anesthesia, which we sincerely hope will serve as an initial process for our journal to become a leader in facilitating the improvement of perioperative management of patients undergoing liver transplantation.…”
mentioning
confidence: 99%